2021
DOI: 10.4269/ajtmh.21-0570
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Compliance with Personal Preventive Measures among Office Workers After Work Resumption during the COVID-19 Outbreak in Pakistan

Abstract: As the lockdowns have been lifted to relieve pressure on the economy, strict adherence to personal preventive measures (PPMs) in offices is essential to control the COVID-19 pandemic. This study investigated self-reported compliance with three PPMs among a sample of office workers in Karachi, Pakistan. A cross-sectional survey with participants were adult office workers who had resumed work in Karachi, Pakistan. All full-time employees aged ≥ 18 years who had resumed work in the offices were invited to complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
3
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
1
3
4
Order By: Relevance
“…The result of our study was lower than other studies done in Ethiopia (49%) and other regions of the world, such as Nepal (37.1 %), China (53.7% ) [40] and (96.8%) [25], Vietnam(75.8%) [41], Japan (90%) [42], Pakistan (46.7%) [43] and Iran (71%) [44]. On the other hand, the current report was higher than a study nding in Thailand (17%) [45].…”
Section: Discussioncontrasting
confidence: 90%
“…The result of our study was lower than other studies done in Ethiopia (49%) and other regions of the world, such as Nepal (37.1 %), China (53.7% ) [40] and (96.8%) [25], Vietnam(75.8%) [41], Japan (90%) [42], Pakistan (46.7%) [43] and Iran (71%) [44]. On the other hand, the current report was higher than a study nding in Thailand (17%) [45].…”
Section: Discussioncontrasting
confidence: 90%
“…The result of our study was lower than other studies done in Ethiopia (49%) and other regions of the world, such as Nepal (37.1 %), China (53.7%)[40] and (96.8%)[25], Vietnam(75.8%)[41], Japan (90%)[42], Pakistan (46.7%)[43] and Iran (71%) [44]. On the other hand, the current report was higher than a study finding in Thailand (17%)[45].…”
Section: Discussioncontrasting
confidence: 85%
“…Japan (90%) [42], Pakistan (46.7%) [43] and Iran (71%) [44]. On the other hand, the current report was higher than a study finding in Thailand (17%) [45].…”
Section: Socio-demographic and Behavioral Characteristics Of Study Pa...contrasting
confidence: 82%
“…As a result, the advertisements were successful in boosting public knowledge about the effectiveness of preventive measures in reducing COVID-19. Subsequently, greater resources for such efforts should be allocated ( 42 ). Furthermore, the other study found that good preventive practices were substantially linked to high COVID-19 preventative measure compliance ( 37 ).…”
Section: Discussionmentioning
confidence: 99%